Insultar con gestos en la Roma antigua y hoy (Minerva, 2019)
This paper deals with the use of some emblemes (i. e., gestures which, in a certain culture, have an inequivocal verbal equivalent) in classical Rome and their survival in the present time. We specifically study emblems which express ridicule and insult. Six gestures are analized; four of them were already used in Rome as mocking or insulting gestures (imitating the stork, the ears of an ass, sticking out the tongue and extending the middle finger); furthemore, two gestures have been included that were used in the Roman Antiquity but did not have the mocking meaning that they convey nowadays (the horn-sign and the fig-sign).
Keywords: Emblemes; gestures; ridicule; insult; imitating the stork; ears of an ass; sticking out the tongue; extending the middle finger; horn-sign; fig-sign